Coexisting frailty and depression associated with low physical activity and quality of life in Saudi community-dwelling older adults: a cross-sectional study - Alhwoaimel, Norah A.; Alqahtani, Bader A.; Alshehri, Mohammed M.; Alhowimel, Ahmed S.; Alenazi, Aqeel M. (Frontiers in Public Health, 2025)
BackgroundFrailty and depression are common conditions in older adults, but their coexistence and combined impact on physical activity and quality of life remain understudied, particularly in Saudi Arabia.ObjectiveTo examine the independent associations of depression, frailty, and their coexistence with physical activity levels and quality of life among Saudi older adults.MethodsA cross-sectional study was conducted among 395 community-dwelling adults aged 60 years and older (mean age 66.4 ± 7.1 years, 60% women) in Saudi Arabia. Frailty was assessed using the FRAIL scale, depression using the Patient Health Questionnaire 9 (PHQ-9), physical activity using the Physical Activity Scale for the Elderly (PASE), and quality of life using the SF-12. Participants were categorized based on the results of FRAIL and PHQ-9 scale into four groups: coexisting frailty and depression, frailty only, depression only, or neither.ResultsThe prevalence of coexisting frailty and depression was 8.6%. Participants with coexisting frailty and depression were more likely to be sedentary (OR = 4.37, 95% CI: 1.41–13.55, p = 0.011) compared to those without frailty or depression. Frailty only group (β = −3.55, p = 0.003) and coexisting frailty and depression (β = −2.55, p = 0.033) were significantly associated with lower physical quality of life. Depression, frailty, and their coexistence were all significantly associated with lower mental quality of life (p < 0.001 for all).ConclusionThe coexistence of frailty and depression in older adults is associated with a higher likelihood of sedentary behavior and lower quality of life. These findings highlight the need for comprehensive geriatric assessments and targeted interventions addressing both physical and mental health in older adults.